2021
DOI: 10.1111/jbg.12539
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships between feed efficiency and gut microbiome in pig lines selected for residual feed intake

Abstract: This study aimed to evaluate the genetic relationship between faecal microbial composition and five feed efficiency (FE) and production traits, residual feed intake (RFI), feed conversion ratio (FCR), daily feed intake (DFI), average daily gain (ADG) and backfat thickness (BFT). A total of 588 samples from two experimental pig lines developed by divergent selection for RFI were sequenced for the 16 rRNA hypervariable V3‐V4 region. The 75 genera with less than 20% zero values (97% of the counts) and two α‐diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 58 publications
6
22
2
Order By: Relevance
“…In chapter 6 it was found that some OTU are highly heritable, with values up to 0.47. This is in line with literature, where values up to 0.50 and 0.57 were found for individual genera (Camarinha-Silva et al, 2017;Aliakbari et al, 2021). However, the microbiota described in chapter 6 that had a high contribution to the prediction of feed efficiency traits, had much lower heritability values.…”
Section: Microbiotasupporting
confidence: 91%
See 2 more Smart Citations
“…In chapter 6 it was found that some OTU are highly heritable, with values up to 0.47. This is in line with literature, where values up to 0.50 and 0.57 were found for individual genera (Camarinha-Silva et al, 2017;Aliakbari et al, 2021). However, the microbiota described in chapter 6 that had a high contribution to the prediction of feed efficiency traits, had much lower heritability values.…”
Section: Microbiotasupporting
confidence: 91%
“…Metabolites that are not used in the body are excreted via the urine, the gastro-intestinal tract, or to the air as CO 2 . Thus, we may hypothesize that variation in individual phenotypes for feed efficiency traits is associated with individual differences in blood metabolite profiles, in addition to being associated with differences in faecal microbiota composition as recently observed (Camarinha-Silva et al, 2017;Aliakbari et al, 2021).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Phenotypic records and faecal samples (604 pigs) were collected from the two last generations (G9 and G10) of two experimental French Large White pig lines that were developed over 11 generations of divergent selection for RFI during 18 years at INRAE (UE GenESI, Surgères, France, https://doi.org/10.15454/1.5572415481185847E12 ), as described in Aliakbari et al [ 12 ]. The structure of the lines and the selection process are described in Aliakbari et al [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The only ASV associated with H-RFI in the stool environment was classi ed as a Ruminococcaceae UCG-005. Members of this family were correlated with FCR of low e cient pigs (McCormack et al, 2017;Aliakbari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%